The Impact of Islamic Education on Local Communities in Indonesia: Systematic Literature Review - Karim, Syaban Abdul; Suprapto, Suprapto; Quddus, Abdul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Islamic education has a vital role in shaping the character and culture of local communities in Indonesia. This study specifically aims to examine the influence of Islamic education on the social, cultural, and educational dynamics within local communities in Indonesia through the Systematic Literature Review (SLR) approach, focusing on the stages of identification, selection, and synthesis of relevant studies. The study identifies and synthesizes findings from multiple related studies published over the past ten years. In this study, 94 articles were identified through Google Scholar, but after a selection process based on inclusion and exclusion criteria, 25 articles were selected for further analysis. Based on a thorough analysis of 25 selected articles, the study results demonstrate that Islamic education contributes significantly to social and cultural change, strengthening local values and fostering an adaptive curriculum. In addition, Islamic education also plays a vital role in countering radicalism and promoting social harmony. However, there are challenges in integrating traditional values with modern educational needs. The study provides in-depth insights for policymakers and educators to develop more effective and responsive education strategies to the needs of local communities in Indonesia.